Pengaruh Waktu Inkubasi Terhadap Daya Hambat Ekstrak Daun Binahong Pada Cutibacterium Acnes - Alvista, Valentina Nancy; Sibero, Hendra Tarigan; Aditya, Muhammad; Apriliana, Ety (CV. Jasa Sukses Abadi, 2024)
Acne (Acne vulgaris) is a common skin disorder often caused by the bacterium Cutibacterium acnes. Bacterial resistance to antibiotics used in acne treatment has become a significant concern. This study evaluated the effect of incubation time on the diameter of the inhibition zone produced by binahong (Anredera cordifolia) leaf extract in inhibiting the growth of C. acnes. The well diffusion method was employed using extract concentrations of 25%, 50%, 75%, and 100%. Data analysis was conducted using a paired t-test. The results showed a significant difference (p < 0.001) in the inhibition zones formed based on variations in incubation time. The findings indicated that longer incubation times resulted in larger inhibition zones. Binahong leaf extract was found to be effective in inhibiting the growth of C. acnes, particularly at higher concentrations and with longer incubation durations. These results demonstrate the potential of binahong leaf extract as an effective acne treatment to address antibiotic resistance.